Ethical issues in Finnish-Russian relations: Finnish perspective - Gennady Polonsky; Erja Turunen (Journal for East European Management Studies, 1996)
This paper explores the role which western, particularly Finnish companies play in shaping the moral and ethical environment of Russian business. The authors evaluate changes in attitudes and behaviour in Russia, comparing the situation before the introduction of market reform with the developments since. Based on empirical data and interviews conducted in Finland, the authors show that there are at least three groups of problems: Firstly, the low business culture of Russian entrepreneurs, secondly, the question how far Finnish companies can go in adapting themselves to the local conditions, and thirdly, the opportunity of Finnish business with Russia to positively affect the moral aspect of the Russian business environment and to gain knowledge about doing business in Russia. – – Der vorliegende Artikel untersucht die Rolle, die westliche (speziell finnische) Firmen bei der Gestaltung des ethischen und moralischen Umfelds des russischen Geschäftslebens spielen. Die Autoren analysieren die Veränderungen von Einstellungen und Verhalten in Rußland, die seit der Einführung marktwirtschaftlicher Strukturen stattgefunden haben. Auf der Grundlage von empirischen Daten und Interviews in verschiedenen finnischen Firmen können die Autoren drei Problemkreise identifizieren: Erstens die geringe Geschäftskultur russischer Unternehmer, zweitens die Frage, wie weit finnische Unternehmen bei der Anpassung an russische Geschäftsbedingungen gehen können, und drittens die Möglichkeiten, die sich aus den Aktivitäten finnischer Firmen ergeben, günstig auf moralische Aspekte des russischen Geschäftslebens einzuwirken und Know-how über das Führen von Geschäften in Rußland zu gewinnen.
Keywords: 650